Hubungan Kendali Glukosa Darah dengan Osteoartritis Lutut pada Pasien DM di RSD Dr. Soebandi - Fitriyah Hardiyanti Astutik; Ali Santoso; Hairuddin Hairuddin (Pustaka Kesehatan, 2014)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia. Incidence of this disease increases in Indonesia, causing an increase chronic complications of DM including ostearthritis. Incidence of knee ostearthritis in DM patient often associated with blood glucose control. The aim of study was to know the relationship between blood glucose control and knee osteoarthritis in DM patients at Dr. Soebandi hospital. This is an observasional study with Cross Sectional design. The research was conducted at Poly Internal Medicine Dr. Soebandi hospital, the population was all patients who come at DM Poly Internal Medicine Dr Soebandi hospital period of September-October 2013, as much as 54 objects. To analyse the relationship between variabels, Chi Squre test (d = 0.05, significant if p˂0.05) was performed. The result showed that the relationship between blood glucose control and knee osteoarthritis was less significat with the value p=0.90 and odd's ratio (OR) of 0.131. It was concluded that there was no corrrelation between blood glucose control and knee osteoarthritis in DM patients at Dr. Soebandi hospital.   Keywords: Diabetes Mellitus, blood glucose control, knee osteoartritis